The legitimacy of precision livestock farming - Isabelle, Adjani (2021)
Precision livestock farming (PLF) is gaining popularity in the Agri sector across the world. The aim of this paper is to understand how PLF is perceived by researchers involved in the development phases as well as looking at PLF from a product category legitimacy framework developed by Bork et al. (2015). The research was conducted with semi-structured interviews with 5 researchers from the Swedish University of Agricultural Science and the RISE research institute. The analysis of the material shows a lack of common understanding regarding the purpose of PLF from different researchers. The material also highlights the potential that PLF has for all production. This includes both small and large-scale farms, although small-scale farms might be facing bigger implementation barriers than large-scale farms. Regarding access to data for PLF, access is limited and there is little regulation as of yet for data ownership and data sharing. The material shows that PLF as a product category is not fully legitimized yet but still fulfils some legitimacy criteria.